2008
DOI: 10.1089/scd.2007.0154
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Human Placenta- and Bone Marrow–Derived Multipotent Mesenchymal Stem Cells

Abstract: Bone marrow is the traditional source of human multipotent mesenchymal stem cells (MSCs), but placenta appears to be an alternative and more readily available source. This study comprehensively compared human placenta-derived MSC (hpMSC) and human bone marrow-derived MSC (hbmMSC) in terms of cell characteristics, optimal growth conditions and in vivo safety specifically to determine if hpMSC could represent a source of human MSC for clinical trial. MSC were isolated from human placenta (hpMSC) and human bone m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
247
2
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 344 publications
(268 citation statements)
references
References 37 publications
(38 reference statements)
13
247
2
2
Order By: Relevance
“…In contrast to bone marrow aspirates, term placenta is a physically large starting tissue (typically 500-750 g 4 ), which can be harvested aseptically during cesarean section with no risk to the donor. MSC derived from placenta have long-term proliferation 5 and immunomodulatory capacity 6 , superior to bone marrow-derived MSC. In a previous study, we demonstrated that a single term placenta contained sufficient MSC for the manufacture of up to 7,000 clinical doses 4 .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to bone marrow aspirates, term placenta is a physically large starting tissue (typically 500-750 g 4 ), which can be harvested aseptically during cesarean section with no risk to the donor. MSC derived from placenta have long-term proliferation 5 and immunomodulatory capacity 6 , superior to bone marrow-derived MSC. In a previous study, we demonstrated that a single term placenta contained sufficient MSC for the manufacture of up to 7,000 clinical doses 4 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, it is essential to have a source of stem cells that have high therapeutic potential and are easily accessible for clinical use. Extra-embryonic fetal tissues, such as the placenta, are readily available either from termination of pregnancy or surplus tissue at routine prenatal diagnostic procedures [17,18], or at term delivery [19,[20][21][22]. Recently, we have shown human fetal early chorionic stem cells (e-CSC) isolated from human placental tissue accelerated tissue repair in dermal excision skin wounds and improved bone quality and plasticity in oim mice.…”
Section: Introductionmentioning
confidence: 99%
“…10 Mechanical as well as enzymatic methods for MSC isolation from different regions of human placenta of different gestational ages were reported (Table 1, see references therein). 5,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Knowledge about vitality, karyotype, phenotype and expandability of such placenta-derived MSC isolates is a prerequisite for therapeutic application, however systematic investigations into reliability of this MSC source and phenotypic stability have not yet been attempted. Further, former reports on placenta-derived MSCs often lack information about the karyotype of the cell isolates.…”
Section: Introductionmentioning
confidence: 99%